Design and performance of a novel high-efficiency WO₃-based combustion catalyst and its catalytic mechanism - Dong, Shuai (2023)
To develop efficient combustion catalyst for solid propellants, a novel WO3-based composite (CuX-WO3/Biochar) was designed by the method of doping and loading. As a dopant, Cu has the advantages of producing multiple bands, inhibiting grain growth and restraining exciton–exciton collisions. Meanwhile, biochar is cheap and available as a carrier, which can effectively inhibit the agglomeration of nanomaterials. Therefore, in this work, Cu-doped WO3 nanoparticles were uniformly anchored on surface of biochar by in-situ solvothermal reaction combined calcination method, which significantly increased the surface-active area, and was firstly applied to catalytic decomposition and laser ignition of ammonium perchlorate (AP), 1,3,5-trinitro-1,3,5-triazacyclohexane (RDX) and 5,5′-bistetrazole-1,1′-diolate (TKX-50). With the introduction of CuX-WO3/Biochar, decomposition peak temperature of AP, RDX and TKX-50 diminished by 97.0, 6.7 and 37.9℃, and activation energy decreased by 14.4, 93.5 and 22.6 kJ mol−1, respectively. Simultaneously, flame brightness, flame area and flame propagation speed during combustion of RDX and TKX-50 were evidently improved after CuX-WO3/Biochar was added. Finally, electron transfer mechanism of catalytic thermal decomposition of energetic materials was deduced based on Density Functional Theory (DFT) calculation and characterization analysis. This study will provide a new insight into development of combustion catalysts.